The Dynamics of Secondary Victimization: When Social Workers Blame Mothers. (July 2020) - Fleckinger, Andrea
The article describes the main results from a qualitative research project, which analyzes the relations between mothers exposed to gender-based violence and child protection social workers, looking at the risk of secondary victimization. The issue emerged from 10 years' experience as a social worker at a women's shelter where I was required several times to mediate the difficult relationship between child protection social worker and mother. The starting point was a preliminary field research with peers (staff members of women's shelters) and women who had been blamed for the violence by their child protection social worker. These results formed the basis for the interviews held with child protection social workers. The analysis shows how victim–offender dynamics might also influence social work practices and illustrate the connections between dynamics of secondary victimization and the expectations regarding mothers and victims. Furthermore, some positive examples of support emerged which could be used as a basis for developing targeted methods for social work practice.